Unmasking the causal relationships latent in the interplay between occupant's actions and indoor ambience: A building energy management outlook. (15th March 2019) - Pal, Monalisa; Alyafi, Amr Alzouhri; Ploix, Stéphane; Reignier, Patrick; Bandyopadhyay, Sanghamitra
Highlights: Offers a case study with real data & a method to implicate users with energy system. Records different types of data from an office room, fitted with multiple sensors. Seeks for an optimal energy-efficient routine to satisfy the occupants' objectives. Compares optimal & historical routines to create explanations for motivating users. Differential explanations with influence unveil causal impact of occupants' actions. Abstract: Assiduous attention to building energy management is essential as the building sector contributes hugely to global energy consumption. Zero cost human-based energy retrofit planning is a promising solution as it can be applied to the existing buildings. Aside from a few works on obtaining optimal retrofits, studies on the impact of occupants' actions are scarce. The primary objective of this work is to demonstrate how the changes in occupants' actions, towards Pareto-optimality, can be beneficial for a better indoor ambience and thereby, associating the users with the energy systems. The proposed approach considers the context, documented by sensors, of an office at Grenoble Institute of Technology, France. Utilizing this data, approximation-guided evolutionary multi-objective optimization algorithm (AGE-II) generates actions by minimizing thermal dissatisfaction, air quality dissatisfaction, heater energy consumption and interference with the daily routine. The optimal and historical plans are compared to reveal the causality of the energy systems that are influenced by occupant's actions. These explanations develop awareness of the effect of changing occupants' actions to an optimal plan by presenting to the occupants the reasons for such changes. Hence, the proposed work helps the occupants to perceive the impact of actions which allow them to adapt their habits to a more energy-efficient routine.